Social media success for every brand : the five storybrand pillars that turn posts into profits - Diaz-Ortiz, Claire, 1982- (HarperCollins Leadership, 2019)
Most business owners are blindly guessing at their social media strategy, and it's costing them time and money. Based on Donald Miller's bestselling book Building a StoryBrand, Claire Diaz-Ortiz applies the seven principles of the StoryBrand Framework to help you build an effective, long-lasting social media plan for your brand. Social Media Success for Every Brand teaches readers how to incorporate the StoryBrand 7-Part Framework into their social media channels to increase engagement and see better results. Social Media Success for Every Brand does not require the reader to be familiar with Building a StoryBrand but provides enough foundation to prepare the reader for practical success with their social media content. Together with the StoryBrand Framework, Claire's SHARE model will help boost customer engagement and grow the organization's brand awareness and revenues. -- Amazon.